The Influence of Human Resource Development on the Performance of Staff at the Pompengan River Region Office in Jeneberang Makassar - Hikmasari Hikmasari; Muchriady Muchran; Muhammad Akib (Journal Social Society, 2026)
In the context of increasing demands for public sector accountability and performance, human resource development (HRD) has become a critical factor in enhancing employee productivity and organizational effectiveness. However, empirical evidence on the role of HRD in improving employee performance, particularly within public institutions in developing countries, remains limited. This study aims to examine the effect of human resource development on employee performance at the Pompengan Jeneberang River Basin Authority Office in Makassar, Indonesia. The research employs a quantitative approach with a descriptive design to analyze the relationship between variables. The population consists of 103 employees, with a sample of 82 respondents determined using the Slovin formula. Data were collected through structured questionnaires, observations, and documentation, and analyzed using descriptive statistics, validity and reliability tests, simple linear regression, and hypothesis testing (t-test). The results indicate that human resource development has a positive and statistically significant effect on employee performance. This is evidenced by a regression coefficient of 0.538 and a t-value of 7.580, exceeding the critical value at a significance level of 0.05. Furthermore, the coefficient of determination (R² = 0.418) shows that 41.8% of the variation in employee performance can be explained by HRD, while the remaining 58.2% is influenced by other factors not examined in this study. These findings underscore the importance of continuous employee development programs in improving work quality, discipline, productivity, and overall organizational effectiveness. The study contributes to the human resource management literature by providing empirical evidence on the strategic role of HRD in public sector organizations. In conclusion, strengthening HRD initiatives is essential for achieving sustainable improvements in employee performance and organizational outcomes.